Efektivitas Pendekatan Pendidikan Matematika Realistik Indonesia (PMRI) untuk Meningkatkan Minat dan Hasil Belajar Matematika Siswa - Rizki Asrarul Mufidah; Agus Setiawan; Isnaini Nur Azizah; Choirudin Choirudin (Numerical: Jurnal Matematika dan Pendidikan Matematika, 2026)
Low levels of students’ interest and achievement in mathematics are often associated with instructional methods that are abstract and insufficiently connected to real-life contexts. This study aimed to examine the effectiveness of the Indonesian Realistic Mathematics Education approach in enhancing students’ engagement and achievement in solving systems of linear equations in two variables. A quasi-experimental design with a nonequivalent control group was employed involving eighth-grade students at a private junior high school in Central Lampung Regency. The sample consisted of two classes selected using cluster random sampling, with one class assigned as the experimental group and the other as the control group. Data were collected through a validated learning-interest questionnaire and a reliable mathematics achievement test, and were analyzed using Multivariate Analysis of Variance (MANOVA). The findings revealed that students who learned through the Indonesian Realistic Mathematics Education approach demonstrated higher levels of learning interest and mathematics achievement than those in the control group. These results indicate that the Indonesian Realistic Mathematics Education approach is effective in promoting active learning and strengthening students’ ability to model and solve contextual mathematical problems.